2007
DOI: 10.1111/j.1365-294x.2006.03149.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographic concordance in the southeastern United States: the flatwoods salamander, Ambystoma cingulatum, as a test case

Abstract: Well-supported, congruent phylogeographic and biogeographic patterns permit the development of a priori phylogeographic and distributional predictions. In the southeastern Coastal Plain of the United States, the common discovery of east-west disjunctions (phylogeographic breaks and species' distributional boundaries) suggests that similar disjunctions should occur in codistributed taxa. Despite the near ubiquity of these disjunctions, the most recent morphological analyses of the flatwoods salamander, Ambystom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 53 publications
3
69
0
Order By: Relevance
“…Much more surprising is the deep phylogeographic break found on either side of the Apalachicola River estuary, with over 5% divergence among mtDNA lineages on either side. The Apalachicola River is a well-known barrier to gene flow for terrestrial organisms (Donovan, Semlitsch, & Routman, 2000;Pauly, Piskurek, & Shaffer, 2007) and freshwater fish (Bagley, Sandel, Travis, Lozano Vilano, & Johnson, 2013;Bermingham & Avise, 1986;Nedbal, Allard, & Honeycutt, 1994;Wooten & Lydeard, 1990), but this is to our knowledge the first reported case for a similar phylogeographic break in a marine fish, although at least one marine mollusk, the arrow squid (Loligo plei), was found to show a break there as well (Herke & Foltz, 2002).…”
Section: Phylogeography and Historical Demography Of Naked Gobiesmentioning
confidence: 98%
“…Much more surprising is the deep phylogeographic break found on either side of the Apalachicola River estuary, with over 5% divergence among mtDNA lineages on either side. The Apalachicola River is a well-known barrier to gene flow for terrestrial organisms (Donovan, Semlitsch, & Routman, 2000;Pauly, Piskurek, & Shaffer, 2007) and freshwater fish (Bagley, Sandel, Travis, Lozano Vilano, & Johnson, 2013;Bermingham & Avise, 1986;Nedbal, Allard, & Honeycutt, 1994;Wooten & Lydeard, 1990), but this is to our knowledge the first reported case for a similar phylogeographic break in a marine fish, although at least one marine mollusk, the arrow squid (Loligo plei), was found to show a break there as well (Herke & Foltz, 2002).…”
Section: Phylogeography and Historical Demography Of Naked Gobiesmentioning
confidence: 98%
“…Additional, detailed sampling of many western U.S taxa, especially aquatic and semiaquatic amphibian and reptile endemics from across their ranges, have further identified within-species patterns of genetic differentiation that may be quite general, or may represent idiosyncratic patterns of single species (Shaffer et al 2000(Shaffer et al , 2004aRecuero et al 2006;Phillipsen and Metcalf 2009;Spinks et al 2010). However, as recently emphasized by several authors, the broad patterns that occasionally emerge from comparative phylogeography (for example, the Apalachicola river discontinuity in the southeastern US [Walker and Avise 1998;Soltis et al 2006;Pauly et al 2007], or the virtually ubiquitous split across the transverse range that separates southern from central California [Calsbeek et al 2003;Chatzimanolis and Caterino 2007]) depend on detailed, single species analyses (Phillipsen and Metcalf 2009;Polihronakis and Caterino 2010). The generality of these landscape-level patterns, and thus their overall utility in conservation planning, should be tested with additional, rangewide work on codistributed taxa.…”
Section: Introductionmentioning
confidence: 94%
“…The H. retardatus population probably shrank during glacial periods and expanded during interglacial periods, and land submergence during interglacial periods likely lim- ited their dispersal. It has been suggested that such divergence, caused by periods of submergence, also suggested occurred among the flatwoods salamander, Ambystoma species, of the coastal plains of the southeastern United States (Pauly et al, 2007).…”
Section: Discussionmentioning
confidence: 99%